2011
DOI: 10.1073/pnas.1019591108
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide prevents axonal degeneration by inducing HIF-1–dependent expression of erythropoietin

Abstract: Nitric oxide (NO) is a signaling molecule that can trigger adaptive (physiological) or maladaptive (pathological) responses to stress stimuli in a context-dependent manner. We have previously reported that NO may signal axonal injury to neighboring glial cells. In this study, we show that mice deficient in neuronal nitric oxide synthase (nNOS −/− ) are more vulnerable than WT mice to toxin-induced peripheral neuropathy. The administration of NO donors to primary dorsal root ganglion cultures prevents axonal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 41 publications
1
39
1
Order By: Relevance
“…However when treated with a neuronal nitric oxide synthase (nNOS) inhibitor the neurons lost their ability to induce EpoR expression in hypoxia and thus were not protected (104). In line with this finding another study demonstrated that nNOS knockout mice are more susceptible to peripheral neuropathy than their wild type counterparts due to the absence of NO-mediated activation of HIF-1 and subsequent downstream neuroprotection by Epo (105). Ex vivo experiments showed that protection recovered by using low doses of NOS donors was almost completely abrogated by Epo siRNA.…”
Section: Neuroprotection By Epo In Vitrosupporting
confidence: 73%
“…However when treated with a neuronal nitric oxide synthase (nNOS) inhibitor the neurons lost their ability to induce EpoR expression in hypoxia and thus were not protected (104). In line with this finding another study demonstrated that nNOS knockout mice are more susceptible to peripheral neuropathy than their wild type counterparts due to the absence of NO-mediated activation of HIF-1 and subsequent downstream neuroprotection by Epo (105). Ex vivo experiments showed that protection recovered by using low doses of NOS donors was almost completely abrogated by Epo siRNA.…”
Section: Neuroprotection By Epo In Vitrosupporting
confidence: 73%
“…There is compelling evidence that HIF-1α can be upregulated by various stimuli other than hypoxia (12)(13)(14)(15)(16)(17)(18). In addition, recent studies directly revealed that HIF-1α contributes to NO-mediated Epo production in normoxic condition (35). Nevertheless, we cannot fully exclude the possibility that weak expression of HIF-2α, which was below the detection limit in our immunoblotting methods, may also contribute to Epo upregulation in our model.…”
Section: Discussioncontrasting
confidence: 40%
“…The stimulatory role of NO in Epo production was previously reported in models using pharmacological methods to increase NO production. For instance, inclusion of S-nitroso-N-acetyl-DL-penicillamine, an NO donor, to primary rat dorsal root ganglion cultures upregulates Epo transcription in glial cells in a HIF-1α-dependent fashion (35). In addition, daily injections of sodium nitroprusside, a generator of NO, significantly increased serum Epo levels (36).…”
Section: Discussionmentioning
confidence: 99%
“…The structurally related fungal sesquiterpenes pycnidione, epolone A, and epolone B induce erythropoietin expression via HIF-1a activation (Cai et al, 1998;Wanner et al, 2000). In a study of cultured dorsal root ganglia, it was found that neuronal NO induces the HIF-1-dependent expression of erythropoietin in adjacent Schwann cells, and the erythropoietin in turn protects axons of the neurons against neurotoxin-induced degeneration (Keswani et al, 2011). In contrast with the Nrf2 stress response pathway, far fewer studies have investigated the effects of phytochemicals on the HIF-1 pathway (Table 2).…”
mentioning
confidence: 99%